A novel strategy to determine the compositions of inorganic elements in fruit wines using ICP-MS/MS. (30th November 2019) - Fu, Liang; Shi, Shuyun
Highlights: A novel multi-elemental analysis of fruit wine was performed using ICP-MS/MS. Spectral overlap was overcome using O2 /H2 and NH3 /He/H2 as mixed reaction gases. Samples were directly analyzed after dilution and acidification. Effects of ethanol on the ICP-MS/MS analyte signal intensity were investigated. Abstract: The composition of inorganic elements is a key factor in determining the quality of fruit wines. However, the use of direct sample injection is challenging for multi-elemental analysis of fruit wine samples. In this paper, an analytical method using inductively coupled plasma tandem mass spectrometry (ICP-MS/MS) was established for determining multiple elements (Al, V, Cr, Mn, Fe, Co, Ni, Cu, Zn, As, Se, Cd, Hg, and Pb) in fruit wine. The fruit wine was diluted using ultrapure water and acidified with nitric acid before injecting into the ICP-MS/MS. Spectral interferences in the complex matrix composition of different fruit wine samples, in the MS/MS mode, were eliminated using mixed reaction gases of O2 /H2 and NH3 /He/H2 through the mass shift and on-mass methods. The limits of detection ranged from 0.41 to 58.1 ng L −1 . This study demonstrates a new approach for multi-elemental analysis in fruit wine with great convenience and high accuracy.